Efeito antimutagênico do extrato de Pyrostegia venusta (Ker Gawl.) Miers nanoestruturado em lipossoma e nanopartícula polimérica - Zanco, Patrícia (2018)
Pyrostegia venusta (Ker Gawl.) Miers is a plant commonly used in the treatment of leucoderma or vitiligo. Its biological potential involves the presence of compounds from its secondary metabolism, such as flavonoids that have antioxidant potential, capable of reducing and/or preventing cellular damage. The association of nanotechnology with plant extracts aims at enhancing the pharmacological activity of plant extracts. In this context, liposomes and polymeric nanoparticles containing ethanolic extract of P. venusta were developed that were physicochemically characterized in relation to the average particle diameter, polydispersity index, pH and zeta potential (ξ). The presence of flavonoids apigenin, luteolin, myricetin, quercetin-3-β-d-glucoside and rutin by LCMS/MS were identified. The chemoprotective effect of ethanolic extract of free and nanostructured P. venusta leaves at the concentration of 1.0 mg/mL (m/v) against chemically induced damage to ADN was evaluated through the in vivo Micronucleus Test. The male Swiss mice were treated via gavage with the nanostructured extracts, crude extract and free nanostructures for 15 consecutive days and were treated with Nethyl-N-nitrosurea (ENU, 50.0 mg/kg) intraperitoneally at the 15th day of treatment. The results demonstrated that the nanostructured extracts (LPEPV and NPEPV) significantly reduced (p≤ 0.05) the frequency of micronuclei in bone marrow cells when compared to their respective positive controls and free extract (EPV), potentiating the chemoprotective effect of P. venusta. Biochemical analyzes for changes in serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatinine (CR) were performed in animals treated with P. venusta nanostructured and free and showed no changes during treatment. Thus, in the conditions performed, the ethanolic extract of P. venusta presented a biological potential in the prevention of the stage of initiation of carcinogenesis.